Hearing Aid Use and Adherence to Treatment in a Publicly-Funded Health Service from the City of São Paulo, Brazil - Iwahashi, Juliana Harumi; Jardim, Isabela de Souza; Shirayama, Yoshihisa; Yuasa, Motoyuki; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2015)
Introduction Periodic follow-up appointments are important to ensure long-term effectiveness of rehabilitation with hearing aids. However, not all users are able to maintain adherence to recommendations prescribed during the fitting process and some do not attend those appointments, which compromises the effectiveness of treatment.Objective Compare hearing aid use after 1 year between subjects who did not attend a follow-up evaluation appointment at a publicly-funded health service (nonattenders) and those who attended the appointment (attenders). Reasons for nonuse of hearing aids and unscheduled appointments were also analyzed.Methods Prospective observational cross-sectional study. Nonattenders and attenders in a follow-up evaluation appointment were interviewed by telephone about hearing aid use, reasons for nonuse, and unscheduled appointments.Results The nonattenders group consisted of 108 subjects and the attenders group had 200 subjects; in both groups, most users kept bilateral use but the nonuse rate was higher in nonattenders. The main reason for nonuse of hearing aids among nonattenders was health problems; fitting problems was the main reason for nonuse in the attenders group. Health problems and issues like unavailable companion and transportation difficulties were the reasons for unscheduled follow-up appointments.Conclusion Nonattenders had a greater nonuse rate and were more likely to abandon hearing aid use. Measures to increase hearing aid use and adherence to prescribed recommendations are also necessary to ensure long-term effectiveness of rehabilitation with hearing aids.
Keywords: hearing aids; public health; patient compliance